Comparison of spontaneous labour with induced labour in nulliparous women using modified WHO partograph - Yadav, Pramila; Verma, Menka; Harne, Sumedha; Sharma, Megha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Childbirth is the period from the onset of regular uterine contraction until expulsion of placenta. The process by which this normally occurs is called labour. Induction of labour is the artificial initiation of uterine contraction prior to their spontaneous onset, leading to progressive dilatation and effacement of the cervix and delivery of the baby. Labour induction is indicated where the benefits to either the mother or the fetus outweighs the benefit of continuing pregnancy. The aim and objectives of the study was to study the progress of labour in nulliparous women who are having spontaneous labour and in those with induced labour in terms of augmentation of labour, mode of delivery, neonatal outcome and maternal complication. Methods: This was a randomized comparative study. The study was conducted in department of Obstetrics and Gynaecology at a tertiary care private centre during time period of May 2014 to May 2015 on 120 pregnant women divided into two groups i.e. A and B consisting of 60 women each. All women were nulliparous and ≥ 37 weeks of gestation age. Those women who had spontaneous onset of labour and reached ≥ 4cm cervical dilatation were included in group A and those who were induced with 25 mcg misoprostol vaginally and reached ≥ 4cm of cervical dilatation were included in group B. Progress of labour was monitored by Modified WHO partograph. Results: The mean duration of labour after 4cm of cervical dilation in spontaneous labour onset group was 5.43 hours and in the induced group was 5.41 hours with p value0.865, which was statistically not significant. In spontaneous labour onset group, 39.3% of patients required augmentation of labour with oxytocin compared to 69% of induced group (p value-0.001). More women had vaginal delivery in spontaneous onset labour group (73.3%) comparative to induced group (53.3%) with pvalue-0.023. There was less caesarean section among those in spontaneous labour than induced labour (20% versus 41.7%) (p=0.010).While most women of induced labour cases reached or crossed action line compared to spontaneous labour (35% versus 16.7%) p=0.022 ,there were more cases in spontaneous labour moving between alert and action line (23.3% versus 10%) p=0.049 .Neonatal outcome and maternal complications were similar in both the group . Conclusions: We conclude from this study that requirement of augmentation for progress of labour was more in induced group, rate of caesarean section was also high but it does not adversely affect the neonatal outcome and maternal complication if labour is monitored with Modified WHO partograph.